Inclusive scaling for gender equality in land, food and water systems, CGIAR GENDER 2025 conference reflections - Mokhema, Seipati; Nortje, Karen (International Water Management Institute, 2025)
Released following the CGIAR Gender Conference held on October 7 – 9, 2025 in Cape Town, South Africa. Under the theme “Accelerating quality in Land, Food and Water Systems,” IWMI researchers highlight that scaling innovations are not only about expanding reach or numbers, but about ensuring equity as innovations move from pilot to wider adoption. Scaling processes must actively mitigate unintended consequences for women, youth, and other marginalized groups through inclusive methodologies and monitoring mechanisms.